Analisis Perkembangan Financial Technology Peer To Peer (P2P) Lending Syari’ah Di Indonesia Dalam Perspektif Maqasid Syari’ah - Polindi, Miko; Darmawansyah, Trisna Taufik; Yanti, Elsa April (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2022)
Peer to Peer (P2P) sharia lending is a type of fintech used by sharia fintechs that utilize technology services. This research aims to analyze the development of fintech peer to peer lending sharia using the maqashid sharia approach. The method used in this research is a qualitative method with a qualitative descriptive approach, through three stages, namely orientation, exploration and focused literature study. The results of this research show that there are seven types of sharia peer to peer lending registered at the OJK, and of the seven P2P lending fintech, the mechanism used is by the MUI DSN Fatwa No: 117/DSN-MUI/II /2018 regarding information technology-based financing services based on sharia principles, this shows that fintech P2P Sharia Lending in Indonesia has fulfilled the maqasid of sharia and has clear legal protection. However, what is needed now is efforts to increase literacy about P2P Sharia Lending in the community.